How would I solve this question:

If $$E_n = \frac{1}{2} + \frac{1}{4} + \frac{1}{6}+ \cdots +\frac{1}{2n}$$ and $$A_n = (2n+1)(E_n)(E_{n+1})$$ Find $$\sum_{n = 1}^{\infty}\frac{1}{A_n}$$

My try: We know that $$E_n = \frac{H_n}{2}$$ where $H_n$ is the harmonic series. So $$\sum_{n = 1}^{\infty}\frac{1}{A_n} = \sum_{n = 1}^{\infty}\frac{4}{(2n+1)(H_n)(H_{n+1})}$$ And I managed to simplify $$\frac{1}{(H_n)(H_{n+1})} = (n+1)\left(\frac{1}{H_n} - \frac{1}{H_{n+1}}\right)$$

But that's how far I've gotten. I get stuck after this. Any help/hints is greatly appreciated.


math.SE, my sincere apologies, but the question was written wrong, $A_n$ is supposed to be $$(2n+2)(E_n)(E_{n+1})$$ not $$(2n+1)(E_n)(E_{n+1})$$ which as you can see from my work makes the summation a lot simpler and easier to find a closed form for.

A derivation on how to solve the problem: $$\begin{align} \sum_{n = 1}^{\infty}\frac{1}{A_n} &= \sum_{n = 1}^{\infty}\frac{4}{(2n+2)(H_n)(H_{n+1})} \\ &= \sum_{n = 1}^{\infty}\frac{4}{(2n+2)}*(n+1)*\left(\frac{1}{H_n} - \frac{1}{H_{n+1}}\right) \\ &= \sum_{n = 1}^{\infty}2\left(\frac{1}{H_n} - \frac{1}{H_{n+1}}\right) \\ &= 2\left(\frac{1}{H_1}\right) \\ &= 2 \end{align}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.